2022
DOI: 10.58421/misro.v1i3.42
|View full text |Cite
|
Sign up to set email alerts
|

Economic Behavior of Fisherfolks that Govern their Decisions to Practice Accounting: Evidence from Probit Models

Abstract: The study reveals the economic behavior of fisherfolks that governs their decisions to practice accounting in Partido district, Camarines Sur, Philippines. Economic behavior was modeled and measured through the following parameters: the socioeconomic characteristics of the fisherfolks and their economic transactions; the economic perceptions on socioeconomic contribution, market sustainability, and financial viability of fishing activity; the recordkeeping practices they adopt and constraints they encounter; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…In general, the study's result showed that the participants agreed that their standard of living was in excellent condition and could meet their necessities. According to Onsay et al (2022), most fisherfolks earn less than the poverty line, indicating that they belong to the poor or low-level income earners. According to Alvina (2022), the earnings of fisherfolks are only enough for their day-to-day lives.…”
Section: Agreementioning
confidence: 99%
“…In general, the study's result showed that the participants agreed that their standard of living was in excellent condition and could meet their necessities. According to Onsay et al (2022), most fisherfolks earn less than the poverty line, indicating that they belong to the poor or low-level income earners. According to Alvina (2022), the earnings of fisherfolks are only enough for their day-to-day lives.…”
Section: Agreementioning
confidence: 99%